Online Learning Infrastructure: Does it Strengthen the Effect of Service Quality on Student Satisfaction? - Novi Marlena; Renny Dwijayanti; Finisica Dwijayati Patrikha; Saino (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
One of the main obstacles to online learning is learning infrastructure and the availability of internet facilities, i.e., internet quotas. Universitas Negeri Surabaya (UNESA) students regularly receive internet quota assistance from the Minister of Education and Culture and Universitas Negeri Surabaya. Therefore, it is expected that the online learning process will run well. The study aimed to determine 1) the impact of the online learning service quality on student satisfaction and 2) the moderation effect of Infrastructure to strengthen the effect of service quality on student satisfaction in online learning. The subjects of this study were students of the UNESA, Indonesia, with 250 students as research samples. Data collection was done by distributing online questionnaires using google forms. The data analysis technique used moderated regression analysis. The results proven that 1) the online learning service quality affects student satisfaction, 2) infrastructure as the moderator variable not proven as a moderator model, but infrastructure has a direct influence on student satisfaction in online learning. Keywords: Online Learning Infrastructure, Students Satisfaction, Learning Quality